ACUTE TOXICITY of SODIUM SELENITE and SODIUM SELENATE TO TILAPIA, Oreochromis niloticus, FINGERLINGS - Ranzani-Paiva, Maria Jose T.; Lombardi, Julio Vicente; Goncalves, Adriano [UNESP] (Inst Pesca, 2011)
Selenium is an essential nutrient for many organisms, including fish. It can be released in the water by natural processes of dissolving rocks and minerals, and by the wastewater from industries and agricultural activities, which can increase its concentration in the environment, leading to toxic effects to the aquatic biota. Median Lethal Concentrations (LC(50-96h)) of two forms of selenium were estimated to fingerlings of Nile tilapia Oreochromis niloticus, focusing on estimating indicators for future environmental risk assessments in aquatic ecosystems contaminated with those elements, particularly for evaluate sources of water quality suitable for rearing tilapia. The results were: LC(50-96h) of sodium selenite (Na(2)SeO(3)) = 4.42 mg Se(4+) L(-1), and LC(50-96h) of sodium selenate (Na(2)SeO(4)) = 14,67 mg Se(6+) L(-1). According to those data, it was possible to classify sodium selenite as highly toxic and sodium selenate as moderately toxic to fingerlings of tilapia.
Keywords: Selenium; aquatic toxicology; fish; aquaculture